Loading and evaluation of meloxicam and atorvastatin in carrageenan microspherical aerogels particles - Mohammad Alnaief, Rana Obaidat, Hadeia Mashaqbeh (Journal of Applied Pharmaceutical Science, 2019)
In this work, the potential of using microspherical aerogel particles based on commercial carrageenan as a drug vehicle was evaluated. Carrageenan hydrogel microparticles were prepared following the emulsion gelation approach. After the successive solvent exchange, supercritical CO2 drying procedure was employed to obtain aerogel microspherical particles. Meloxicam and atorvastatin (class II drug) were loaded into the aerogel matrix by adsorption from their corresponding supercritical CO2 solution. All preparations were characterized by their physicochemical properties. In vitro drug released was investigated for the drug-aerogel formulation to assist the effect of aerogel technology on the release profile of the targeted drug. Meloxicam and atorvastatin model drugs maintained their crystalline structure. Significant enhancement in the release profile of meloxicam after loading in the carrageenan aerogel can be related to de-aggregation of meloxicam inside the particle, while no enhancement in atorvastatin release was observed. Results were indicative of a failure in the loading of atorvastatin inside the carrageenan particle at the selected experimental processing parameters.
Keywords: Carrageenan aerogel, meloxicam, atorvastatin, supercritical fluid technology, drug loading.